Ideology of Translation “Discover Bengkulu the Land of Rafflesia” - Pebri Prandika Putra (AL LUGHAH, 2018)
Ideology in the translation process is important in deciding towards what kind of direction the translation will go. If the primary purpose of the translation is to promote the culture, it is considered adequate to choose the foreignization over the domestication as the ideology of the translation when it comes to the translation of culture-specific items. However, deciding what ideology should be used in the translation process is complicated. There are many factors that can affect the ideology of a translation. Both ideologies can lead to totally different results of the accuracy of the meaning of the translations. This research was content analysis of Historical Book Discover Bengkulu The Land of Rafflesia. This research show that there are two ideologies that appeared in this translation such as foregnization ideology where oriented to source language and domestication ideology where oriented to target language.